Written in the stars ebook A novel. - Bellefleur, Alexandria (2020)
"I was hooked from the very first page!" – Christina Lauren, New York Times bestselling author of In a Holidaze "This book is a delight." – New York Times Book Review A National Bestseller and winner of the Lambda Literary Award for Best Lesbian Romance! Featured on Shondaland, Oprah Mag, Bustle, The New York Times Book Review, Buzzfeed, POPSUGAR, Entertainment Weekly, Washington Post, NPR, Culturess, Vulture, and more. Named one of the Best Romances of 2020 by Washington Post, Bustle, and Buzzfeed! With nods to Bridget Jones and Pride & Prejudice, this debut is a delightful queer rom-com about a free-spirited social media astrologer who agrees to fake a relationship with a grumpy actuary until New Year's Eve—with results not even the stars could predict! After a disastrous blind date, Darcy Lowell is desperate to stop her well-meaning brother from playing matchmaker ever again. Love—and the inevitable heartbreak—is the last thing she wants. So she fibs and says her latest set up was a success. Darcy doesn't expect her lie to bite her in the ass. Elle Jones, one of the astrologers behind the popular Twitter account Oh My Stars, dreams of finding her soul mate. But she knows it is most assuredly not Darcy... a no-nonsense stick-in-the-mud, who is way too analytical, punctual, and skeptical for someone as free-spirited as Elle. When Darcy's brother—and Elle's new business partner—expresses how happy he is that they hit it off, Elle is baffled. Was Darcy on the same date? Because... awkward. Darcy begs Elle to play along and she agrees to pretend they're dating. But with a few conditions: Darcy must help Elle navigate her own overbearing family during the holidays and their arrangement expires on New Year's Eve. The last thing they expect is to develop real feelings during a faux relationship. But maybe opposites can attract when true love is written in the stars? "Everything I want from a rom-com: fun, whimsical, sexy." – Talia Hibbert, USA Today bestselling author of Get a Life, Chloe Brown